Canada. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The Inter-American Institute for Cooperation on Agriculture (IICA), Cooperative Research and Technology Program for the Northern Region approved grants for seven collaborative research projects in Mexico, Brazil, St. Kitts and Nevis, St. Lucia, Trinidad and Tobago and Ecuador. Research topics include the development of diagnostic tools, risk assessment and management, traceability methods and molecular epidemiological strategies. In addition, the Institute has submitted a formal project to Global Affairs Canada to leverage the capabilities of satellite data and remote sensing technologies to empower livestock farmers in Guatemala and Mexico. It has also provided technical cooperation services in Canada, participating in food waste reduction challenges and advising agricultural and diplomatic committees. The Institute has co-organized regional and hemispheric seminars and international conferences, established partnerships with governments and universities, conducted virtual courses on agri-food exports, collaborated with various organizations in regional and hemispheric seminars, and participated in international conferences to share knowledge and solutions in agricultural and environmental development.